A quasi-experimental study of effects of community health workers’ incentivisation on uptake of maternal, newborn and child health services in Lamu County, Kenya - Kilonzo, Henry; Ebole, Gilbert; Oyore, John P.; Olulo, Millicent; Tole, Victor; Mwangi, Peris (International Journal Of Community Medicine And Public Health, 2023)
Background: Community health workers (CHWs) are known as the ‘gate keepers’ of good health in the community. Being the first contact with the patients at the community level, they can help improve the maternal, newborn and child health (MNCH) indicators if they are well motivated to conduct their day-to-day work. At the same time, MNCH indicators are negatively affected by hard-to-reach health facilities and cultural factors thus the CHWs can help improve the health status in this category. Methods: The study utilized a quasi-experimental study design with an intervention and a control site in both Lamu West and Lamu East Sub Counties. Purposive sampling used to select study population and study site. Study period was (August 2018-March 2022). Mixed methods approach was used with both quantitative and qualitative methodologies of data collection to enable data triangulation. Questionnaires were used to collect data from CHWs, focused group discussions with caregivers and In-depth Interviews conducted with key informants from the Ministry of Health- Lamu County and the implementing partner-PharmAccess. Results: The study established that 78% of the CHWs were selected by the community members. Most of the CHWs in the intervention site had attended other trainings after the initial capacity development program, had at least one supervision in the last month preceding evaluation, were satisfied with the community and county appreciation. The difference between control and intervention site had a statistical significance (p<0.05) for report writing during home visits, cross-referencing of reports before submission, attendance of refresher courses, loss of interest to work as a CHW and referral of patients to link facilities. Conclusions: CHWs need motivation in delivering their services. This can be done in form of incentives (both monitory and non-monitory), refresher trainings and supportive supervision.